Roles of adenine methylation and genetic mutations in adaptation to different temperatures in Serratia marcescens - Matthieu Bruneaux; Ilkka Kronholm; Roghaieh Ashrafi; Tarmo Ketola (Epigenetics, 2022)
Epigenetic modifications can contribute to adaptation, but the relative contributions of genetic and epigenetic variation are unknown. Previous studies on the role of epigenetic changes in adaptation in eukaryotes have nearly exclusively focused on cytosine methylation (m5C), while prokaryotes exhibit a richer system of methyltransferases targetting adenines (m6A) or cytosines (m4C, m5C). DNA methylation in prokaryotes has many roles, but its potential role in adaptation still needs further investigation. We collected phenotypic, genetic, and epigenetic data using single molecule real-time sequencing of clones of the bacterium Serratia marcescens that had undergone experimental evolution in contrasting temperatures to investigate the relationship between environment and genetic, epigenetic, and phenotypic changes. The genomic distribution of GATC motifs, which were the main target for m6A methylation, and of variable m6A epiloci pointed to a potential link between m6A methylation and regulation of gene expression in S. marcescens. Evolved strains, while genetically homogeneous, exhibited many polymorphic m6A epiloci. There was no strong support for a genetic control of methylation changes in our experiment, and no clear evidence of parallel environmentally induced or environmentally selected methylation changes at specific epiloci was found. Both genetic and epigenetic variants were associated with some phenotypic traits. Overall, our results suggest that both genetic and adenine methylation changes have the potential to contribute to phenotypic adaptation in S. marcescens, but that any environmentally induced epigenetic change occurring in our experiment would probably have been quite labile.